Akuntabilitas Dana Desa dalam Perspektif Transparansi, Kapasitas Aparatur, dan Tata Kelola - Nurul Mizna Sukma; Ningrum Trija Kesuma; Sisi Maghfirah Rahmah Sembiring (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to systematically review the development of research related to the accountability of village fund management by highlighting the role of transparency, apparatus capacity, and village governance. The method used is a Systematic Literature Review (SLR) of empirical articles published in national and international journals from 2019 to 2024. The review process was conducted in a structured manner through the stages of formulating research questions, searching for literature, selecting articles, and thematic synthesis. The results of the study indicate that the system of village fund management is still in its early stages of development, with limited research on the accountability of village fund management. The review process was conducted in a structured manner through the stages of formulating research questions, literature search, article selection based on inclusion and exclusion criteria, and thematic synthesis. The results of the study indicate that internal control systems and village governance are the most consistent factors affecting the accountability of village funds, while transparency and apparatus capacity show varying findings across studies. Differences in regional context, level of assistance, and implementation of regulations were the main causes of inconsistency in the results. These findings emphasise the need for a holistic and integrative governance approach to improve the accountability of village fund management in a sustainable manner.